"Jawi dan Milenia" an animated documentary:rotoscoping approach. - Nur Adilah, Azaha (2015)
The Jawi script has been side-line slowly after the nation achieved its independence.The education system was formed based on Razak Education Commision Report.On the other hand,people choose to watch the documentary from overseas rather than local because they felt that overseas documentaries have idea,creativity and interesting visual than local's.Thus,an animated documentary is produced to ensure the acceptance of conveying the message of the importance of Jawi script to the respondents.Rotoscope animation techniques were implemented to some parts of the documentary which entitled 'Jawi dan Milenia'('Jawi and Milenia'),attempting to attract the audiences' attention.An interview was conducted to four students of Multimedia to test the acceptance of animated documentary as the medium to convey the message about the Jawi script.Based on this study and collected data,it has indicate that the animated documentary is well accepted by the chosen respondents.In conclusion,the message in 'Jawi dan Milenia' is well-conveyed by using animated documentary with the implementation of rotoscoping technique.